Current thinking about the management of dysfunction of the temporomandibular joint: a review. Issue 4 (May 2017) - Rajapakse, S.; Ahmed, N.; Sidebottom, A.J.
Abstract: Increasingly the management of TMJ pathology is becoming a subspecialist interest. The number of patients having TMJ joint replacement had steadily increased over the last decade and there is now NICE guidance on this matter. Whilst the evidence of the management of TMJ disease is limited and there are few randomised controlled trials, the incidence of TMJ pathology has not changed and there is a requirement for guidance on the management. Whilst previously patients with TMJ pain were managed surgically, this is changing, and the vast bulk of initial management is non-surgical/medical. This paper will review the literature on TMD and provide guidance for management.